2018
DOI: 10.1002/ep.13027
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pollutants Removal from Industrial Wastewaters Using a Novel Bioflocculant Produced by Bacillus licheniformis NJ3

Abstract: This study deals with the potential of bioflocculant for the treatment of various industrial wastewaters. Bioflocculant (BFBl) produced by Bacillus licheniformis NJ3, showed 97% flocculating activity in primary screening (kaolin assay). The characteristics of the BFBl such as temperature and pH stability, cation‐independency makes the flocculation process more economic as harmful coagulants and stabilizers are not required. BFBl efficiently treated synthetic wastewaters as compared to alum by reducing turbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…An unstable intermediate is produced during this transition (Cr 5+ ), which is controlled by NADH/NADPH [151]. Numerous studies Nguema et al [152] and Joshi et al [153] indicated that B. licheniformis removed 95% and 69.4% of Cr. Over 81% of the Cr was eliminated by B. cereus.…”
Section: Cr Remediationmentioning
confidence: 99%
“…An unstable intermediate is produced during this transition (Cr 5+ ), which is controlled by NADH/NADPH [151]. Numerous studies Nguema et al [152] and Joshi et al [153] indicated that B. licheniformis removed 95% and 69.4% of Cr. Over 81% of the Cr was eliminated by B. cereus.…”
Section: Cr Remediationmentioning
confidence: 99%